Determinant Analysis of Hypertension in Type 2 Diabetes Mellitus Patients: A Cross-Sectional Study in Medan, North Sumatera, Indonesia - Tjendera, Mariaman; Gusbakti; Chiuman, Linda; Mukti, Ade Indra; Sartika, Dewi (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Type 2 diabetes mellitus (T2DM) and hypertension are two chronic conditions that frequently co-occur and pose a significant health burden. At Padang Bulan Primary Healthcare Center in Medan, out of 260 Prolanis participants, 117 T2DM patients sought treatment, and 90 of them were diagnosed with hypertension. This study aimed to analyze the determinants of hypertension in T2DM patients receiving care at Padang Bulan Primary Healthcare Center in Medan. Subjects and Method: An analytical cross-sectional study was conducted on 100 T2DM patients selected through consecutive sampling. Data were collected using structured question¬naire, anthropometric measurement, and blood pressure and blood glucose examinations. The variables studied included sociodemographic characteristics (gender, education, occupation, marital status) and clinical characteristics (body mass index, duration of T2DM, blood glucose levels, family history). Data analysis was performed using Chi-square test. Results: The majority of respondents were women (62%), highly educated (79%), and obese (87%). The prevalence of hypertension in T2DM patients was notably high (>70%) across all groups. However, bivariate analysis showed no statistically significant relationship between any of the studied variables and the incidence of hypertension (p>0.05). Conclusion: There was no significant relationship between sociodemographic and clinical factors with the incidence of hypertension in T2DM patients. Nevertheless, the high prevalence of hypertension indicates the importance of a comprehensive approach in managing both conditions